Knockdown of eIF3a attenuates the pro-fibrogenic response of hepatic stellate cells induced by TGF-Î²1 - He, P; Yu, Z-J; Sun, C-Y; Jiao, S-J; Jiang, H-Q (Cellular and Molecular Biology, 2016)
Activation of hepatic stellate cells (HSCs) plays an important role in the development of liver fibrosis. The eukaryotic translation initiation factor (eIF) 3a is the largest subunit of the eIF3 complex and has been involved in pulmonary fibrosis. However, the role of eIF3a in liver fibrosis remains largely unknown. Therefore, in this study, we investigated the role of eIF3a in transforming growth factor-Î²1 (TGF-Î²1)-induced HSC activation. Our results demonstrated that the expression of eIF3a was up-regulated in human liver fibrotic tissues and activated HSCs. In addition, knockdown of eIF3a suppressed TGF-Î²-induced HSC proliferation and the expression of Î±-smooth muscle actin (Î±-SMA) and collagen I. Furthermore, knockdown of eIF3a inhibited the expression of p-Smad3 induced by TGF-Î²1 in HSCs. These results suggest that eIF3a may function as a novel regulator to modulate HSC activation, potentially through inhibiting the TGF-Î²1/Smad3 signaling pathway.